Records of deep-sea anglerfishes (Lophiiformes: Ceratioidei) from Indonesia, with descriptions of three new species - Ho, Hsuan-Ching (Zootaxa, 2016)
An examination of the ceratioid anglerfishes collected on the Indian Ocean side of Indonesia during surveys in 2004–2005 have revealed 18 species in 9 genera and 6 families, including three new species: Cryptopsaras couesii (Ceratiidae); Melanocetus johnsonii (Melanocetidae); Diceratias trilobus, Bufoceratias microcephalus sp. nov., B. thele, B. shaoi, B. cf. wedli (Diceratiidae); Himantolophus danae, H. sagamius, H. nigricornis, H. macroceratoides (Himantolophidae); Oneirodes quadrinema sp. nov., O. amaokai sp. nov., O. carlsbergi, O. cristatus, Dermatias platynogaster, Chaenophryne cf. melanorhabdus (Oneirodidae); and Linophryne parini (Linophrynidae). Of these, specimens of B. shaoi, H. macroceratoides, O. cristatus and L. parini represent the second records since the species were described. A specimen of H. nigricornis represents the third record and a specimen of Dermatias platynogaster represents the fourth record. Descriptive data and notes on the geographical distribution and morphological variation are provided for each species.